The Effectiveness of Problem-Solving-Oriented Basic Chemistry Micro-Modules to Improve Students' Critical Thinking Skills - Jusniar, Jusniar; Syamsidah, Syamsidah; Zubair, Sakinah (Jurusan Kimia FMIPA UNM, 2025)
This study aims to evaluate the effectiveness of Problem-Solving-Oriented Basic Chemistry Micro-Modules in enhancing students’ critical thinking skills. The method employed refers to the calculation of N-Gain for each critical thinking indicator, namely interpretation, analysis, inference, deduction, and evaluation. The results indicate that all indicators improved, with the highest gains in deduction (0.59) and evaluation (0.64), categorized as medium–high, while interpretation showed the lowest gain (0.32), categorized as low–medium. These findings suggest that problem-solving-based learning is effective in fostering students’ logical, critical, and reflective thinking, although interpretation still requires additional reinforcement strategies. Therefore, the implementation of micro-modules with a problem-solving orientation is recommended as an innovative approach in basic chemistry instruction to strengthen students’ higher-order thinking skills.